1998
DOI: 10.1016/s0002-9440(10)65540-x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Human Atheroma Contain PPARγ

Abstract: Mononuclear phagocytes play an important role in atherosclerosis and its sequela plaque rupture in part by their secretion of matrix metalloproteinases (MMPs), including MMP-9. Peroxisomal proliferator-activated receptor gamma (PPARgamma), a transcription factor in the nuclear receptor superfamily, regulates gene expression in response to various activators, including 15-deoxy-delta12,14-prostaglandin J2 and the antidiabetic agent troglitazone. The role of PPARgamma in human atherosclerosis is unexplored. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(95 citation statements)
references
References 35 publications
0
94
1
Order By: Relevance
“…Rexinoids activate RXR in PPAR heterodimers, thereby mimicking some effects of PPAR activation. PPAR␥, which is almost absent in normal arteries, has been shown to be expressed in atherosclerotic lesions in human and mouse (12)(13)(14). Previous in vitro studies suggested a key role of PPAR␥ in inducing macrophage differentiation and foam cell formation (13,15).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Rexinoids activate RXR in PPAR heterodimers, thereby mimicking some effects of PPAR activation. PPAR␥, which is almost absent in normal arteries, has been shown to be expressed in atherosclerotic lesions in human and mouse (12)(13)(14). Previous in vitro studies suggested a key role of PPAR␥ in inducing macrophage differentiation and foam cell formation (13,15).…”
Section: Resultsmentioning
confidence: 98%
“…(C) Representative photographs of atherosclerosis in the aorta of apoE Ϫ͞Ϫ mice, a relevant section from an untreated apoE Ϫ͞Ϫ mouse (control), and an equivalent section of an apoE-deficient mouse after receiving GW2331 (PPAR␣͞␥ coagonist) or LG100364 (RXR agonist). production of matrix metalloproteinases (14), vascular cell adhesion molecule, and intercellular adhesion molecule (19). Furthermore, PPAR␥ agonists are reported to inhibit migration of vascular smooth muscle cells (20) as well as monocyte͞ macrophage homing (19) to atherosclerotic plaques.…”
Section: Resultsmentioning
confidence: 99%
“…PPARγ has had inhibitory effects on VSMC proliferation and migration133, 134 as well as EC growth and migration 135. PPARγ activation reduces monocyte recruitment to atherosclerotic plaques 136. PPARγ also has a modulatory effect on inflammation and is known to decrease monocyte/macrophage production of several inflammatory cytokines 137.…”
Section: Implication Of Noncanonical Wnt Signaling In Vcmentioning
confidence: 99%
“…scavenger receptor expression such as CD36 (4, 6, 7), and this led to the supposition that PPAR␥ activation may promote foam cell formation, a known atherogenic process characterized by cholesterol ester droplet accumulation in macrophages (27). In this experiment, we further investigated the influence of both Cy-3-g and Pn-3-g on AcLDL-induced transformation of mouse peritoneal macrophages into foam cells.…”
Section: Treatment Of Anthocyanin Alone Does Not Influence Foam Cell mentioning
confidence: 99%